2008
DOI: 10.1007/s00449-007-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of an improved continuous parallel shaken bioreactor system for three microbial model systems

Abstract: A continuous parallel shaken bioreactor system, combining the advantages of shaken bioreactors with the advantages of continuous fermentation, was specifically manufactured from quartz glass and provides a geometric accuracy of <1 mm. Two different model systems (facultative anaerobic bacterium C. glutamicum, and Crabtree-negative yeast P. stipitis), whose growth behaviour and metabolite formation are affected by dilution rate and oxygen availability, were studied. The transition from non-oxygen to limited con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…15, 85748 Garching, Germany e-mail: d.weuster-botz@lrz.tum.de; D.Weuster-Botz@lrz.tu-muenchen.de URL: http://www.mw.tum.de/biovt/ combines the advantages of shaken bioreactors with continuous fermentation [1]. The next paper is from the group of Dirk Weuster-Botz (Intitute of Biochemical Engineering at the Technical University of Munich, Germany), who was the head of fermentation group at the Institute of Christian Wandrey from 1991 to 1999.…”
Section: Weuster-botz (And)mentioning
confidence: 99%
“…15, 85748 Garching, Germany e-mail: d.weuster-botz@lrz.tum.de; D.Weuster-Botz@lrz.tu-muenchen.de URL: http://www.mw.tum.de/biovt/ combines the advantages of shaken bioreactors with continuous fermentation [1]. The next paper is from the group of Dirk Weuster-Botz (Intitute of Biochemical Engineering at the Technical University of Munich, Germany), who was the head of fermentation group at the Institute of Christian Wandrey from 1991 to 1999.…”
Section: Weuster-botz (And)mentioning
confidence: 99%
“…A number of miniaturized, mostly stirred parallel bioreactor systems were introduced which partly allow a quasi-continuous operation. During the past six decades, many types of continuous reactor systems have been introduced (Evans, Herbert, and Tempest, 1970;Walther et al, 1994;Gu et al, 1996;Whiteley, Brown, and McLean, 1997;Horiuchi et al, 2003;Lamping et al, 2003;Akgun et al, 2004;Zhang et al, 2006;Akgun et al, 2008). Several reviews and papers pioneering the theoretical analysis of continuous culture systems have subsequently been published by various authors (Moser, 1958;Herbert, 1961;Malek, 1960;Herbert, Elsworth, and Telling, 1965;Malek and Fencl, 1966;Betts and Baganz, 2006).…”
Section: Continuous Shaken Bioreactormentioning
confidence: 95%
“…The first generation of the continuous parallel shaken bioreactor system consisted of four special reactor vessels modified from the 250 mL Erlenmeyer flasks. Akgun et al (2008) recently demonstrated the applicability of continuous parallel bioreactor system, with well-defined reactor geometry with six parallel bioreactors. This assembly was termed as "CosBios system.…”
Section: Continuous Shaken Bioreactormentioning
confidence: 99%
See 1 more Smart Citation
“…A novel approach for continuous culture based in a shaken reactor system was also developed and later improved [64][65][66][67]. The novel bioreactor system is basically composed by specially designed 250-mL shake flask with two inlets and one outlet.…”
Section: Simple Shaken Vessels As Small Scale Bioreactorsmentioning
confidence: 99%